Analysis of the Istidlal Method in the Concept of Livelihood according to Imam Ibn Hazm's Perspective - Abdillah Afabih (Indonesian Journal of Islamic Law, 2023)
Islam has provided detailed regulations on marriage, from the marriage proposal (akad), agreement (akad), to the fulfillment of rights and obligations between husband and wife. All these statements are based on the Quran and Hadith. One of the husband's obligations towards his wife is to provide a living (support payments). Fiqh scholars unanimously agree that livelihood is the responsibility of the husband, regardless of his wealth, poverty, or middle ground. However, Imam Ibn Hazm has a unique and different viewpoint from the consensus of the scholars. He argues that the responsibility of providing a living actually shifts to the wife due to the husband's incapability. Based on this unique perspective, this research aims to analyze "How is the concept of livelihood understood in the perspective of Imam Ibn Hazm and the istidlal method used in that concept?" In this research, a qualitative analysis method with a literature review approach will be used. Data will be collected through the analysis of relevant works by Imam Ibn Hazm concerning the concept of livelihood, as well as through the analysis of works by other scholars and related literature. The istidlal method will be applied to understand the arguments and viewpoints of Imam Ibn Hazm regarding the concept of livelihood. The main findings of this research will summarize Imam Ibn Hazm's perspective on the concept of livelihood and the role of istidlal in supporting his viewpoint. The research will identify the main arguments used by Imam Ibn Hazm to support his viewpoint, as well as the implications of his viewpoint on the understanding of the concept of livelihood in Islam. This research will conclude that Imam Ibn Hazm's perspective on livelihood and the use of the istidlal method to support his viewpoint make significant contributions to the understanding of the concept of livelihood in Islam. The implications of Imam Ibn Hazm's perspective on contemporary Islamic family law thinking will also be discussed.